THE PREFERRED OF ATTRACTANT PLANT AS ACTIVITY PLACE of Aedes aegypti IN THE LABORATORY - Agustina, Elita; Kamal, Samsul; Nisa, Khairun (Universitas Syiah Kuala, 2025)
This research aimed to determine the preferences and activities of Aedes aegypti toward attractant plants in the laboratory. This was a descriptive observational study using the visual control method. The data were analyzed using descriptive statistics. The results showed that the highest presence of male (50%) was found on Mangifera indica, followed by Murraya sp. (23%), Ixora sp. (11%), Annona muricata (11%), Plumeria sp. (3%) and Pteridium aquilinum (2%). The highest presence of female (65%) was found on Mangifera indica, followed by Murraya sp. (9%), Ixora sp. (9%), Plumeria sp. (9%), Annona muricata (4%), and Pteridium aquilinum (4%). The feeding activity of both male and female was highest on Mangifera indica and lowest on Ixora sp., Pteridium aquilinum, and Annona muricata. Resting activity was observed on all test plants except Pteridium aquilinum. The Mangifera indica has a high attraction for both male and female Ae. aegypti for feeding and resting activities.